Business Engineering for Modern World - Sorooshian, Shahryar (2016)
"Business Engineering (BE)" places an emphasis on the unique combination of Engineering and Business. BE merge the knowledge of 'Business decision makings' and 'Engineering problem solving' allowing business to gain the competitive edge in technically oriented economy and dynamic business environment. This talk will discuss the issues of the BE in our modern world.